THE USE OF SIMPLE PAST TENSE VERB AND PERSONAL PRONOUN IN WRITING RECOUNT TEXT - Rina Hasanah; Mashadi Said (INFERENCE: Journal of English Language Teaching, 2020)
The aim of the research is to know the use of simple past tense verb and personal pronoun in writing recount text. The method of this research is Dulay’s Surface Strategy Taxonomy. The result of the classification was calculated by the frequency and the percentage of each error: 1) The error of simple Past Tense Verb is 247which consist of, the lowest is 14 errors or 5,6% % for Misordering, 18 errors or 38,2 % for addition, 59 errors or 23,8% for omission and The highest 156 errors or 63,1% for Misinformation. 2) The error of using Pronouns in writing recount text the writer found the total error is 17. The highest error is misordering which consists of 14 errors or 82,3%, the second error is misinformation  consist of 2 errors or 11,7%. The third error is addition consist of 1 errors or 5,8%, and the last place is omission, it is there is no found error.